Evaluation of OMNIgene Sputum and Ethanol Reagent for Preservation of Sputum Prior to Xpert and Culture Testing in Uganda - Ardizzoni, Elisa; Orikiriza, Patrick; Ssuuna, Charles; Nyehangane, Dan; Gumsboga, Mourad; Taremwa, Ivan Mugisha; Turyashemererwa, Esther; Mwanga-Amumpaire, Juliet; Langendorf, Céline; Bonnet, Maryline (Journal of Clinical Microbiology, 2019)
Xpert MTB/RIF (Xpert) and culture are the most reliable methods for tuberculosis diagnosis but are still poorly accessible in many low-resource countries. We aimed to assess the effects of OMNIgene Sputum (OM-S) and ethanol in preserving sputum for Xpert and OM-S for mycobacterial growth indicator tube (MGIT) testing over periods of 15 and 8days, respectively. Sputum samples were collected from newly diagnosed smear-positive patients. For Xpert, pooled samples were split into 5 aliquots: 3 for Xpert on days 0, 7, and 15 without additive and 2 with either OM-S or ethanol at day 15. For MGIT, 2 aliquots were tested without preservative and 2 with OM-S at 0 and 8days. Totals of 48 and 47 samples were included in the analysis for Xpert and culture. With Xpert, using day 0 as a reference, untreated samples stored for 7 and 15days showed concordances of 45/46 (97.8%) and 46/48 (95.8%). For samples preserved with OM-S or ethanol for 15days compared with untreated samples processed at day 0 or after 15days, OM-S concordances were 46/48 (95.8%) and 47/48 (97.9%), while those of ethanol were 44/48 (91.7%) and 45/48 (93.8%). With MGIT, concordances between untreated and OM-S-treated samples were 21/41 (51.2%) at day 0 and 21/44 (47.7%) at day 8. In conclusion, Xpert equally detected tuberculosis in OM-S-treated and untreated samples up to 15days but showed slightly lower detection in ethanol-treated samples. Among OM-S-treated samples, MGIT positivity was signiﬁcantly lower than in untreated samples at both time points.
Keywords: OMNIgene; Tuberculosis; Xpert; Culture